Flood management strategies in frequent and small scale events: lessons learned from Amarante (Portugal). - Tedim, Fantina; Carvalho, Salete (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2010)
The 2000/2001 winter was exceptionally rainy in Portugal and between November 2000 and March 2001 several floods occurred. In this period some localities registered the highest floods of the last hundred years. One example is the town of Amarante, in the north of Portugal, that has been affected by several flood events during the time frame previously mentioned. There is no reference of these episodes in the international disaster databases (e.g. Em-data, Darmouth Flood Observatory) because it is a very small scale event, and no fatalities were recorded. However, it is a recurrent situation with considerable direct and indirect damages which affects a small part of the cultural heritage centre which is also an important touristic and commercial area. The objective of this paper is to understand the characteristics of flood risk in Amarante which is a product of the hazard and the vulnerability of exposed elements (e.g. people, environment and structures) in order to improve flood disaster management efficiency. The paper is organized into two parts. On the first one we add new data to the previous knowledge through the identification of flood episodes in two time periods, between 1937 and 1955 and from 1985 to 2001. Each event was characterized according to several parameters (e.g. flood peak, water height, flooding area, duration, and flow velocity) and classified into six levels according to flood magnitude (water height), flooded area (extension) and potential impacts (damages). This approach improves hazard knowledge and systematizes emergency response procedures. It can improve the communication, not only between the different civil protection agents, but also between them and the citizens during the emergency. It can also be useful for assurance companies’ policy. The second part is focused on the management of the March 21st 2001 flood which was the most severe in Amarante’s history at least in the last hundred years. Understanding the damages and the impacts of flood on livelihoods, the emergency procedures, as well as the articulation between people and civil protection agents are fundamental to increase the efficiency of flood risk management strategies and the determination of appropriate protection levels.
Keywords: flood; risk management; small scale; urban area; disaster response; Portugal